2021
DOI: 10.3389/fpsyg.2021.645092
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Experiences of Fibromyalgia Patients Involved in the Fimouv Study During COVID-19 Lockdown

Abstract: Introduction: The COVID-19 pandemic implied a period of lockdown for the general population, increasing the risk to develop some physical or mental disorders. In fibromyalgia patients, these disorders are part of the large clinical picture of the syndrome. Fibromyalgia management is especially based on a regular practice of physical activity. Lockdown imposed a break in rhythms, requiring a restructuring of scheduling. Thus, the present study aimed to investigate the experiences of fibromyalgia patients during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 42 publications
4
12
1
Order By: Relevance
“…Although during the pandemic the severity of fibromyalgia was also observed to worsen in a considerable part of the participants [ 7 , 10 12 ], from a theoretical point of view it is unexpected that, on a group level, there was no mean change or even a positive change. This suggests that the negative impact of the COVID-19 pandemic on people with fibromyalgia is weaker than assumed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although during the pandemic the severity of fibromyalgia was also observed to worsen in a considerable part of the participants [ 7 , 10 12 ], from a theoretical point of view it is unexpected that, on a group level, there was no mean change or even a positive change. This suggests that the negative impact of the COVID-19 pandemic on people with fibromyalgia is weaker than assumed.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, people with fibromyalgia during the pandemic thought that their improvement was caused by beneficial effects of smart working and the opportunity to exercise more regularly [ 10 ]. In another study, some interviewed people with fibromyalgia reported that reduced social constraints allowed them to adjust the rhythms of their life to fluctuations of symptoms and that fibromyalgia stopped being a main priority in their lives [ 7 ]. These authors concluded that reducing social constraints could be a key for fibromyalgia management, where symptoms seemed to take less space in everyday life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also noted suboptimal access to health care for the majority of FM patients, and a relatively low utilization of and dissatisfaction related to telehealth. Given that catastrophizing is associated with FM pain and symptom severity (33), it is not surprising that levels of catastrophizing also increased during the pandemic. In fact, our results show that this increase in pain catastrophizing had the strongest association with a worsened perceived ability to cope with pain and a poorer mental health during the pandemic compared to other clinical measures such as changes in pain intensity or FM impact.…”
Section: Discussionmentioning
confidence: 99%
“…These patients had poor quality of life, social relationships, and quality of sleep, which caused a recurrence of the disease and increased anxiety and depression in them (22). In this regard, Colas et al (29) examined the experiences of fibromyalgia patients during the COVID-19 pandemic. Their results showed that the COVID-19 pandemic exacerbated the disease in people with fibromyalgia.…”
Section: Discussionmentioning
confidence: 99%